Adjustment on gibbsite and boehmite co-precipitation from supersaturated sodium aluminate solutions - 王志 杨柳 张娟 郭占成 张懿 (Transactions of Nonferrous Metals Society of China, 2010)
Gibbsite is the usual precipitation product from alumina refineries with either Bayer or sintering process.However,the advantage of boehmite precipitation over gibbsite precipitation is the significant energy saving in the subsequent calcination step.The current investigation takes a pragmatic approach to measure precipitation ratios,determine product phase,morphology and particle size distribution,and assess the impacts and adjustment capability of main parameters such as seed,temperature,ethanol medium,and supersaturation on the precipitation kinetics and alumina hydrate type during co-precipitation process.The results clarify that gibbsite and boehmite both can be precipitated from supersaturated sodium aluminate solutions simultaneously,and the competitive formation between Al（OH）3 and γ-AlOOH determines the main precipitate phases from pregnant liquor.Boehmite seeds,high temperature and ethanol addition can promote the boehmite precipitation and improve the mass fraction of boehmite in products.Co-precipitation changes the multimodal distribution of seeds to a normal and well distribution of products,and the particle size is more than several times that of seeds.